Placenta accreta spectrum: treatment consensus in a resource-limited settingAJOG Global Reports at a Glance - Albaro José Nieto-Calvache, MD; José Enrique Sanín-Blair, MD; Marcela Buitrago, MD; Juliana Maya, MD; Jesús Andrés Benavides, MD (AJOG Global Reports, 2023)
BACKGROUND: Management options for placenta accreta spectrum disorder are multiple, without a clear picture of which one is superior. Management guidelines describe the use of a wide range of human and technological resources that are not always available in resource-limited settings. OBJECTIVE: This consensus seeks agreement on general guidelines that facilitate the management of placenta accreta spectrum in low- and middle-income countries. STUDY DESIGN: Consensus was developed using the modified Delphi methodology, incorporating 3 successive rounds in which 6 dimensions of placenta accreta spectrum treatment were discussed: pathway for placenta accreta spectrum care, roles at different levels of care, organization of the interdisciplinary teams at the reference hospitals, training interdisciplinary teams, placenta accreta spectrum surgical treatment, and management of placenta accreta spectrum patients without prenatal diagnosis. RESULTS: Consensus was achieved on all questions on placenta accreta spectrum management. Specific low- and middle-income countries problems were addressed, trying to establish guidelines for the construction of trained placenta accreta spectrum interdisciplinary teams, as well as the rational use of the different therapeutic options available in a limited resources setting. In addition, it is highlighted the need to facilitate contact between patients affected by this disease and the interdisciplinary groups, overcoming administrative barriers typical of some health systems. CONCLUSION: We present a consensus on the treatment of placenta accreta spectrum in a low- and middle-income countries, based on local experts’ opinions. Construction of high-quality scientific evidence is essential in settings with limited resources.